Development of pickled banana blossoms (Musa sapientum Var. compressa) - España, Maribeth N. (1982)
This study was undertaken to develop a process for pickled banana blossoms using the saba variety. It was divided into three phases based on the proposed process fr the development of the pickled product. To determine the level of sulfite and time of soaking of the banana blossoms for effective inhibition of browning, the banana blossoms were soaked in 0.1%, 0.3% and 0.5% Na2S2O5 solution, each at 5, 10 and 15 minutes soaking. Th sulfited, blanched banana blossoms were the prepared on sweet-sour pickling solutions using the following sugar to vinegar ratios based on the weights of the banana blossoms: 1:1, 2:1, 3:2. The best brix-acid ratio which produced a good blend of sweet and sour flavor was determined. Using the best-brix-acid ratio, 0.1% sorbic acid and 0.1% sodium benzoate were added to the pickling solutions to determine which additive will effectively inhibit microbial growth. In all three phases, the products were subjectively and objectively evaluated. Based on objective and subjective tests, 0.1% Na2S2O5 solution was chosen as it produced the same effect on color as with higher concentrations. However, 15 minutes soaking time was employed to allow for possible reduction in sulfite during blanching and pickling. The blanched, sulfited banana blossoms prepared in pickling solution with 3 parts sugar and 2 parts vinegar was the most preferred based on objective and subjective test results. The addition of 0.1% sorbic acid and 0.1% sodium benzoate to the pickling solutions lowered greatly he microbial load of the pickled products. Thus, additives were considered effective inhibitors of microbial growth.